2018
DOI: 10.1038/s41386-018-0145-2
|View full text |Cite
|
Sign up to set email alerts
|

In vivo biased agonism at 5-HT1A receptors: characterisation by simultaneous PET/MR imaging

Abstract: In neuropharmacology, the recent concept of 'biased agonism' denotes the capacity of certain agonists to target-specific intracellular pathways of a given receptor in specific brain areas. In the context of serotonin pharmacotherapy, 5-HT receptor-biased agonists could be of great interest in several neuropsychiatric disorders. The aim of this study was to determine whether biased agonists could be differentiated in terms of regional targeting by use of simultaneous functional magnetic resonance imaging (fMRI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…It also showed region-specific uptake changes in isoflurane-anesthetized animals, contrary to [ 18 F]MPPF for which global increase throughout the brain was observed (Yokoyama et al, 2016). Top design a radiotracer that would be easier to quantify, the structural analog [ 18 F]F13640 was recently evaluated (Vidal et al, 2018). F13640 also exhibits high selectivity for 5-HT 1A , but intermediate affinity (K i = 1 nM) compared to the previous two attempts.…”
Section: State Of the Art Of Existing Pet Agonist Radiotracers For Nementioning
confidence: 99%
See 2 more Smart Citations
“…It also showed region-specific uptake changes in isoflurane-anesthetized animals, contrary to [ 18 F]MPPF for which global increase throughout the brain was observed (Yokoyama et al, 2016). Top design a radiotracer that would be easier to quantify, the structural analog [ 18 F]F13640 was recently evaluated (Vidal et al, 2018). F13640 also exhibits high selectivity for 5-HT 1A , but intermediate affinity (K i = 1 nM) compared to the previous two attempts.…”
Section: State Of the Art Of Existing Pet Agonist Radiotracers For Nementioning
confidence: 99%
“…Of the numerous attempts to develop a radiotracer sensitive to serotonin release, only a few experiments with [ 11 C]CUMI-101 (Milak et al, 2011) ([ 18 F]F13640 (Vidal et al, 2018) and [ 11 C]Cimbi36 (Jorgensen et al, 2017; Yang et al, 2017) showed sensitivity. These difficulties suggest notable differences between dopamine and serotonin competition systems: degree of receptor availability, proportion of high-affinity state receptors, and size of the accessible receptor pool (Paterson et al, 2010).…”
Section: What Is Different With Antagonist Radiotracers?mentioning
confidence: 99%
See 1 more Smart Citation
“…This could reflect inadequate dosing (Martinez et al, 2000), non-selective effects of pindolol on both 5-HT1A auto- and heteroreceptors (Newman-Tancredi et al, 2001), or antagonism of beta-adrenergic receptors. Partial block of postsynaptic 5-HT1A receptors by pindolol may prevent pindolol’s benefits due to block of 5-HT1A autoreceptors, emphasizing the need for compounds with higher selectivity to block presynaptic or activate post-synaptic 5-HT1A receptors (Garcia-Garcia et al, 2014; Vidal et al, 2018).…”
Section: Serotonin Antidepressants and Depressionmentioning
confidence: 99%
“…Such studies have only recently become feasible. For example, in a recently reported study hybrid PET/MRI has been used to assess receptor occupancy variations and BOLD variations using different 5‐HT1a agonists, in order to evaluate whether it is possible to target different cellular pathways using molecules with similar receptor targeting‐properties, but slightly different binding which will affect molecular/pharmacological responses [Vidal et al, ].…”
Section: Opportunities and Future Directionsmentioning
confidence: 99%